An introduction to secondary data analysis with IBM SPSS statistics - MacInnes, John, 1956- author (Sage Publications Ltd., 2017)
John MacInnes takes the fear out of statistics for students and helps to raise the standards of their quantitative methods skills, by clearly and accessibly introducing all that's needed to know about using secondary data and working with IBM SPSS Statistics.-- Source other than the Library of Congress.